2019
DOI: 10.1017/ice.2019.123
|View full text |Cite
|
Sign up to set email alerts
|

Association between universal gloving and healthcare-associated infections: A systematic literature review and meta-analysis

Abstract: Objective:Healthcare-associated infections (HAIs) are a significant burden on healthcare facilities. Universal gloving is a horizontal intervention to prevent transmission of pathogens that cause HAI. In this meta-analysis, we aimed to identify whether implementation of universal gloving is associated with decreased incidence of HAI in clinical settings.Methods:A systematic literature search was conducted to find all relevant publications using search terms for universal gloving and HAIs. Pooled incidence rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Similar conclusions can be drawn when looking to the most recent meta-analysis, showing how universal gloving may provide a small protective effect on healthcare-associated infections in pediatric/neonatal ICU patients (IRR 0.75; 95% CI, 0.65-0.87), but not in adult ICUs (IRR 1.01; 95% CI 0.91-1.13) [44]. However, this difference may also have been due to different care patterns or increased awareness among healthcare workers when dealing with the pediatric population, and it was not observed in the pooled analysis of RCTs only [44].…”
Section: Universal Gloving and Contact Isolationsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar conclusions can be drawn when looking to the most recent meta-analysis, showing how universal gloving may provide a small protective effect on healthcare-associated infections in pediatric/neonatal ICU patients (IRR 0.75; 95% CI, 0.65-0.87), but not in adult ICUs (IRR 1.01; 95% CI 0.91-1.13) [44]. However, this difference may also have been due to different care patterns or increased awareness among healthcare workers when dealing with the pediatric population, and it was not observed in the pooled analysis of RCTs only [44].…”
Section: Universal Gloving and Contact Isolationsupporting
confidence: 78%
“…Similar conclusions can be drawn when looking to the most recent meta-analysis, showing how universal gloving may provide a small protective effect on healthcare-associated infections in pediatric/neonatal ICU patients (IRR 0.75; 95% CI, 0.65-0.87), but not in adult ICUs (IRR 1.01; 95% CI 0.91-1.13) [44]. However, this difference may also have been due to different care patterns or increased awareness among healthcare workers when dealing with the pediatric population, and it was not observed in the pooled analysis of RCTs only [44]. Moreover, another meta-analysis evaluating discontinuation of contact precautions for MDROs did not find increased infection rates by MRSA and VRE, with discordant results for ESBL and a trend toward an increase in C. difficile infections but with a very low rate of transmission [45].…”
Section: Universal Gloving and Contact Isolationsupporting
confidence: 78%
“…Chang et al reported in a systematic review and metaanalysis of 8 studies that demonstrated that implemented universal gloving alone showed a signifi cant association with decreased incidence of hospital-acquired infections (IRR 0.77; 95% CI 0.67-0.89). 13 Our study also identifi ed a large cluster of 12 patients in a single location, which turned out to be the general medical ward, where there is maximum concentration of patients in the hospital with an open cubicle model, and sharing of a common centralised air system. This could have played a role in the transmission given the predominantly inhalation mode of transmission reported by Jones et al 13 Wong et al 14 reported early in the pandemic from Hong Kong that there was no transmission in a general ward in their hospital after extensive contact tracing and follow up of all the patients and hospital staff who had come into contact with an index case of COVID-19.…”
Section: Discussionmentioning
confidence: 85%
“…13 Our study also identifi ed a large cluster of 12 patients in a single location, which turned out to be the general medical ward, where there is maximum concentration of patients in the hospital with an open cubicle model, and sharing of a common centralised air system. This could have played a role in the transmission given the predominantly inhalation mode of transmission reported by Jones et al 13 Wong et al 14 reported early in the pandemic from Hong Kong that there was no transmission in a general ward in their hospital after extensive contact tracing and follow up of all the patients and hospital staff who had come into contact with an index case of COVID-19. However, that study concentrated on the transmission from a COVID-19 patient to other patients and to the staff members rather than from the staff member to the patients.…”
Section: Discussionmentioning
confidence: 85%
“…Nonetheless, only a handful of small studies have evaluated the use of universal gloving as a method to reduce the incidence of HAI's. In a recent meta-analysis of studies that implemented universal gloving, Chang et al 7 showed a mixed impact on HAI depending on whether universal gloving was implemented alone or as part of intervention bundles.…”
mentioning
confidence: 99%